How Affective Polarization Undermines Support for Democratic Norms. Issue 2 (22nd September 2021) - Kingzette, Jon; Druckman, James N; Klar, Samara; Krupnikov, Yanna; Levendusky, Matthew; Ryan, John Barry
Abstract: Does affective polarization—the tendency to view opposing partisans negatively and co-partisans positively—undermine support for democratic norms? We argue that it does, through two mechanisms. First, in an age of elite polarization, norms have been politicized . This leads affectively polarized partisans to oppose particular constitutional protections when their party is in power but support them when their party is out of power, via a cue-taking mechanism. Second, affective polarization may generate biases that motivate voters to restrict the other party's rights. Using nationally representative surveys, we find strong support for the cue-taking argument. In 2019, with a Republican administration in power, affectively polarized Republicans opposed constitutional protections while affectively polarized Democrats supported them. The reverse was true in 2012 during a Democratic administration. The findings have important, albeit troubling, implications for American democracy, as affective polarization undermines support for basic democratic principles.